2011
DOI: 10.1089/scd.2010.0072
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA hsa-miR-138 Inhibits Adipogenic Differentiation of Human Adipose Tissue-Derived Mesenchymal Stem Cells Through Adenovirus EID-1

Abstract: A better understanding of the molecular mechanisms underlying the differentiation of human adipose tissue-derived mesenchymal stem cells (hAD-MSCs) could provide new insights into the pathogenesis of a number of diseases, such as obesity and diabetes, and broaden the spectrum of potential hAD-MSCs-based cell therapy. In this study, we reported that a human microRNA, hsa-miR-138, could inhibit the adipogenic differentiation of hAD-MSCs. Our results showed that miR-138 was significantly down-regulated during adi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
124
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 168 publications
(129 citation statements)
references
References 41 publications
4
124
0
1
Order By: Relevance
“…Recently, miR-138 was reported as a negative regulator of adipocyte differentiation of human adipose tissue-derived MSCs (28). These data, together with our findings, suggest a general role of miR-138 in the inhibition of hMSC differentiation and maintenance of the undifferentiated state of MSC.…”
Section: Discussionsupporting
confidence: 82%
“…Recently, miR-138 was reported as a negative regulator of adipocyte differentiation of human adipose tissue-derived MSCs (28). These data, together with our findings, suggest a general role of miR-138 in the inhibition of hMSC differentiation and maintenance of the undifferentiated state of MSC.…”
Section: Discussionsupporting
confidence: 82%
“…miR-138 was highly expressed in undifferentiated MSCs and down-regulated upon differentiation to osteoblastic, adipogenic and chondrogenic lineages. Based on its expression profile and functional inhibition of osteogenesis and adipogenesis (77,98), it is thus possible that miR-138 maintains MSCs in undifferentiated stage. Similarly, miR-335 down-regulation was shown to be critical for MSC differentiation, and over-expression of miR-335 inhibited both osteoblastic and adipogenic differentiation of MSCs (99).…”
Section: Role Of Mirnas In Mesenchymal Precursor Cell Differentiationmentioning
confidence: 99%
“…Emerging evidence suggests that miRNAs are involved in regulating differentiation and cell fate decisions [8]. Lots of miRNAs, including miR-143, miR-24, miR-31, miR-30c, miR-642a-3p, miR-141/200a, miR-135, miR-378, miR-196a, miR-27a, miR-26a, miR-125b, miR-133, miR-29b, miR-2861, miR-3960, miR-335-5p, miR-138, and miR-130, have been identified that are involved in the differentiation of adipocytes or osteoblasts [9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Recently, several miRNAs have also been identified to be responsible for the balance of adipogenesis and osteogenesis.…”
Section: Introductionmentioning
confidence: 99%